2017
DOI: 10.1007/s10549-017-4335-0
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of lymphaticovenular anastomosis in breast cancer-related lymphedema

Abstract: IntroductionLymphedema can be a debilitating condition, causing a great decrease in a person’s quality of life (QoL). Treatment with lymphaticovenular anastomosis (LVA), in which an anastomosis is created between the lymphatic and venous system, may attenuate lymphedema symptoms and reduce swelling. In this study, we share the results using LVA to treat breast cancer-related lymphedema (BCRL) at our institution.Materials and methodsPatients were eligible for inclusion if they suffered from unilateral BCRL, if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
83
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(87 citation statements)
references
References 31 publications
3
83
1
Order By: Relevance
“…Consequently, the improvement of patients' QoL is the main goal of lymphoedema treatments (Cornelissen et al, 2017). With the advancement of microsurgical techniques, LVA is gaining popularity and is used as a surgical treatment for extremity lymphoedema regardless of the fact that its clinical profile is not supported by highquality data (Akita et al, 2015;Lee, Laredo, & Neville, 2011;Winters et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, the improvement of patients' QoL is the main goal of lymphoedema treatments (Cornelissen et al, 2017). With the advancement of microsurgical techniques, LVA is gaining popularity and is used as a surgical treatment for extremity lymphoedema regardless of the fact that its clinical profile is not supported by highquality data (Akita et al, 2015;Lee, Laredo, & Neville, 2011;Winters et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Consecutive patient recruitment and the prospective study design were unclear in one study (Poumellec et al, 2017), but the study was still included. Another study was included at first, but excluded after data extraction because of retrospective analysis of patient data (Winters et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four papers reported on LVB outcomes using the LYMQOL (Table 3). Winters et al, in two separate studies-one with 29 patients and 12 month follow up and another with 12 patients and 6 month follow up-compared pre-operative to post-operative LYMQOL surveys in patients with upper extremity lymphedema [36,37]. In both studies, all subscales and the overall quality of life improved significantly (p < 0.01).…”
Section: Lymqolmentioning
confidence: 99%
“…However, studies with a minimum of 1-year followup or longer have still demonstrated promising results confirming the efficacy of this approach for treating lymphedema. [46][47][48] This highlights the need for experience and an indepth understanding of supermicrosurgical techniques, as well as the anatomy and physiology of the lymphatic system. Once the anastomosis is completed, the final outcome and improvement in patient symptoms are obviously dependent on a patent anastomosis.…”
Section: Discussionmentioning
confidence: 99%